Global Research Trends on Student Moral Intelligence: A Bibliometric Review (2003-2023) - Angger Saloko; Aim Abdulkarim; Sapriya Sapriya; Kokom Komalasari (JETL (Journal of Education, Teaching and Learning), 2025)
Educational institutions have a responsibility to provide students with moral understanding to be able to face moral problems in society. Researchers worldwide make various efforts to discover the best strategies and formulate them into a framework for building the moral intelligence of students. This study provides a bibliometric overview of articles published in the Scopus database with the keywords 'moral intelligence' and 'students.'The bibliometric review was conducted using data processing tools, VOSviewer and Publish or Perish (PoP). The obtained data consisted of 17 articles, following five stages of the bibliometric review process: defining search keywords, determining initial search results, refining search results, compiling statistical data, and conducting analysis. The results of the bibliometric review indicate that the publication trends related to the moral intelligence of students globally tend to fluctuate. Iran is the country with the highest number of Scopus-indexed articles on the theme of students' moral intelligence, totaling ten articles. Meanwhile, the most significant citation trend for articles occurred in 2010, with a total of 26 citations. The limited amount of research conducted on the theme of students' moral intelligence presents an opportunity for researchers to explore novelty aspects.